2011
DOI: 10.1530/rep-10-0511
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of conceptus exposure to colony-stimulating factor 2 on survival, elongation, interferon-τ secretion, and gene expression

Abstract: Exposure of bovine conceptuses to colony-stimulating factor 2 (CSF2) from days 5 to 7 of development can increase the percentage of transferred conceptuses that develop to term. The purpose of this experiment was to understand the mechanism by which CSF2 increases embryonic and fetal survival. Conceptuses were produced in vitro in the presence or absence of 10 ng/ml CSF2 from days 5 to 7 after insemination, transferred into cows, and flushed from the uterus at day 15 of pregnancy. There was a tendency (PZ0.07)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 22 publications
0
29
1
Order By: Relevance
“…For the D18 pregnant heifers, mean antiviral activity was 180 000 IU/flush. The obtained antiviral activities appear to be lower than reported earlier, because Short et al [56] found 10 5 IU/flush on D15 and 10 7 IU/flush on D17 and Loureiro et al [57] found up to 6 3 10 6 IU/flush on D15. Altogether, the observed antiviral activity in uterine flushings after the 2 days of IFNA2 administration were in a physiological range comparable to antiviral activity in the uterine lumen during early pregnancy due to production of IFNT by the elongating conceptus.…”
Section: Discussioncontrasting
confidence: 55%
“…For the D18 pregnant heifers, mean antiviral activity was 180 000 IU/flush. The obtained antiviral activities appear to be lower than reported earlier, because Short et al [56] found 10 5 IU/flush on D15 and 10 7 IU/flush on D17 and Loureiro et al [57] found up to 6 3 10 6 IU/flush on D15. Altogether, the observed antiviral activity in uterine flushings after the 2 days of IFNA2 administration were in a physiological range comparable to antiviral activity in the uterine lumen during early pregnancy due to production of IFNT by the elongating conceptus.…”
Section: Discussioncontrasting
confidence: 55%
“…Several uterine- and conceptus-derived factors such as fibroblast growth factors (e.g. FGF2, 10) and colony stimulating factor 2 stimulate IFNT production from bovine trophectoderm [16,18,31,32]. These and other factors may play a part in the rapid increase in IFNT production during elongation.…”
Section: Resultsmentioning
confidence: 99%
“…In cattle and sheep, endometrial derived proteins, e.g. IGFBP1 ), GRP (Song et al 2008), LGALS15 (Lewis et al 2007), CSF2 (Loureiro et al 2011), actively enhance migration, proliferation and/or attachment of the conceptus trophectoderm. Therefore, inhibitors of protein and peptide cleavage in the ULF would be important to ensure that full-length functional forms of at least some of these proteins, when transported from the endometrium into the uterine lumen, are available for use by the elongating conceptus.…”
Section: Discussionmentioning
confidence: 99%